Risk–Benefit assessment of foods: Development of a methodological framework for the harmonized selection of nutritional, microbiological, and toxicological components - Boué, Géraldine; Ververis, Ermolaos; Niforou, Aikaterini; Federighi, Michel; Pires, Sara M.; Poulsen, Morten; Thomsen, Sofie T.; Naska, Androniki (Frontiers in Nutrition, 2022)
Investigating the impact of diet on public health using risk-benefit assessment (RBA) methods that simultaneously consider both beneficial and adverse health outcomes could be useful for shaping dietary policies and guidelines. In the field of food safety and nutrition, RBA is a relatively new approach facing methodological challenges and being subject to further developments. One of the methodological aspects calling for improvement is the selection of components to be considered in the assessment, currently based mainly on non-harmonised unstandardized experts’ judgement. Our aim was to develop a harmonized, transparent, and documented methodological framework for selecting nutritional, microbiological and toxicological RBA components. The approach was developed under the NovRBA project (Novel foods as red meat replacers – an insight using Risk-Benefit Assessment methods), which attempted to estimate the overall health impact of replacing red meat with an edible insect species, Acheta domesticus. Starting from the compositional profiles of both food items, we created a “long list” of food components. By subsequently applying a series of predefined criteria, we proceeded from the “long” to the “short list”. These criteria were established based on the occurrence and severity of health outcomes related to these components. For nutrition and microbiology, the occurrence was evaluated considering the presence of a component in the raw material, as well as the effect of processing on the respective component. Regarding toxicology, the presence and exposure relative to reference doses and the contribution to total exposure were considered. Severity was graded with the potential contribution to the background diet alongside bioavailability aspects (nutrition), the Disability Adjusted Life Years per case of illness of each hazard (microbiology), and disease incidence in the population, potential fatality and lifelong disability (toxicology). To develop the “final list” of components, the “short list” was refined by considering the availability and quality of data for a feasible inclusion in the RBA model. The methodology developed can be broadly used in food RBA, to guide and reinforce a harmonized selection of nutritional, microbiological and toxicological components and will contribute to facilitating RBA implementation, enabling the generation of transparent, robust and comparable outcomes.